2022
DOI: 10.3390/su142416454
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Radiation Characteristics of Sandstone Fracture Seepage under Coupled Stress-Hydro Effect

Abstract: Effective monitoring of rock fracture and seepage is an important information means to ensure the safety of geotechnical engineering. Therefore, sandstone samples were subject to uniaxial compression under different hydraulic conditions in the presence of infrared radiation and observation. This study uses the multiple infrared radiation indexes (ΔAIRT, IRV, VDIIT) and image data to analyze the influence of coupled stress-hydro effect of infrared radiation change on sandstone surface. The main findings are: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Sun et al utilized infrared and acoustic emission combined monitoring to investigate the thermo-acoustic effects during the rock damage process, and the results showed that the VSMIT and the related dimension of the acoustic emission ringing count (Dm) exhibit significant mutation during rock damage and fracture events, with the VSMIT mutation time being earlier than the Dm mutation time in 71.1% of rock samples, indicating that the formation of unstable cracks is the fundamental reason for the mutation in the VSMIT and Dm [45]. Cui et al utilized an infrared thermal camera to monitor sandstone water seepage experiments, and the results revealed a significant mutation in the VOIIT and VSMIT before the sandstone water seepage fracture, with the VSMIT exhibiting pulse-like mutation [46].…”
Section: Variance Of Original Infrared Image Temperature (Voiit) and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Sun et al utilized infrared and acoustic emission combined monitoring to investigate the thermo-acoustic effects during the rock damage process, and the results showed that the VSMIT and the related dimension of the acoustic emission ringing count (Dm) exhibit significant mutation during rock damage and fracture events, with the VSMIT mutation time being earlier than the Dm mutation time in 71.1% of rock samples, indicating that the formation of unstable cracks is the fundamental reason for the mutation in the VSMIT and Dm [45]. Cui et al utilized an infrared thermal camera to monitor sandstone water seepage experiments, and the results revealed a significant mutation in the VOIIT and VSMIT before the sandstone water seepage fracture, with the VSMIT exhibiting pulse-like mutation [46].…”
Section: Variance Of Original Infrared Image Temperature (Voiit) and ...mentioning
confidence: 99%
“…Therefore, the VSMIT is more advantageous for identifying the infrared radiation precursors of bearing coal and rock failure, making it easier to capture the precursors of bearing coal and rock failure. Therefore, the VSMIT is suitable as an indicator for searching for precursors of bearing coal and rock failure [46].…”
Section: Advantages and Disadvantages Of Different Infrared Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under high hydraulic gradients, weak permeable areas form and extend, leading to soil water slurry explosions [10][11][12][13]. The infrared radiation information of rock changes during the process of stress redistribution and consequent fracture damage process [14][15][16][17][18][19][20]. Monitoring the infrared radiation released to the outside during the process of rock loading can predict the characteristics and process of rock deformation and failure.…”
Section: Introductionmentioning
confidence: 99%